2017
DOI: 10.3892/ijo.2017.4080
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine induces TIPE2 upregulation and Stat3 phosphorylation contributes to cholinergic anti-inflammatory effect

Abstract: Cholinergic anti-inflammatory pathway has therapeutic effect on inflammation-associated diseases. However, the exact mechanism of nicotine-mediated anti-inflammatory effect is still unclear. TIPE2, a new member of tumor necrosis factor-α-induced protein-8 family, is a negative regulator of immune homeostasis. However, the roles of TIPE2 in cholinergic anti-inflammatory effect are still uncertain. Here, we demonstrated that nicotine exerts its anti-inflammatory effect by TIPE2 upregulation and phosphorylated st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Interestingly, nicotine can both promote and reduce inflammation. By acting through nAChRs on immune cells, nicotine inhibits the function of the transcription factor nuclear factor-κβ (NF-κB) by increasing the phosphorylation of signal transducer and activator of transcription 3 (STAT3) [123,124]. Conversely, nicotine can activate immune cells by increasing their chemotactic activity, migration, and interaction with endothelial cells, resulting in a heightened inflammatory response [125].…”
Section: Inflammationmentioning
confidence: 99%
“…Interestingly, nicotine can both promote and reduce inflammation. By acting through nAChRs on immune cells, nicotine inhibits the function of the transcription factor nuclear factor-κβ (NF-κB) by increasing the phosphorylation of signal transducer and activator of transcription 3 (STAT3) [123,124]. Conversely, nicotine can activate immune cells by increasing their chemotactic activity, migration, and interaction with endothelial cells, resulting in a heightened inflammatory response [125].…”
Section: Inflammationmentioning
confidence: 99%
“…Co-Immunoprecipitation (Co-IP) was performed according to previous description [ 21 ]. Briefly, BMPC conferred with above treatments was harvested and lysed in the buffer of Pierce™ Co-Immunoprecipitation Kit (Cat.…”
Section: Methodsmentioning
confidence: 99%
“…Whole cellular lysates or the output of Co-IP was subjected to 7–10% SDS polyacrylamide gel electrophoresis (SDS-PAGE) according to previous description [ 21 ]. Briefly, proteins were electrophoretically transferred onto a PVDF membrane (Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the above 2 models, another study showed that nonphosphorylated STAT3 might compete with NF-κB. The inhibition of STAT3 protein expression could enhance cytokine production and eliminate α7nAChR signaling [40]. Furthermore, other studies have found that nicotine increases the level of IL-1 receptor-related kinase M in macrophages, which depends on JAK2, STAT3, and PI3K [47].…”
Section: Color Version Available Onlinementioning
confidence: 99%
“…Nevertheless, studies have shown that nicotine can induce IKK to inhibit the phosphorylation of I-kappa B and the transcriptional activity of NF-κB [32]. Nicotine treatment has been also shown to increase STAT3 phosphorylation and reduce LPS-induced p65 translocation [39,40].…”
Section: Nf-κb Pathwaysmentioning
confidence: 99%